Multimodal Predictions of Super-Refractory Status Epilepticus and Outcome in Status Epilepticus Due to Acute Encephalitis - Yuan, Fang; Yang, Fang; Jia, Ruihua; Li, Wen; Jiang, Yongli; Zhao, Jingjing; Jiang, Wen (Frontiers in Neurology, 2018)
Objective: Status epilepticus (SE) is one of the most critical symptoms of encephalitis. Studies on early predictions of progression to super-refractory status epilepticus (SRSE) and poor outcome in SE due to acute encephalitis are scarce. We aimed to investigate the values of neuroimaging and continuous electroencephalogram (EEG) in the multimodal prediction. Methods: Consecutive patients with convulsive SE due to acute encephalitis were included in this study. Demographics, clinical features, neuro-imaging characteristics, medical interventions, and anti-epileptic treatment responses were collected. All the patients had EEG monitoring for at least 24 hours. We determined the early predictors of SRSE and prognostic factors of three-month outcome using multivariate logistic regression analysis. Results: From March 2008 to February 2018, 570 patients with acute encephalitis were admitted to neurological intensive care unit (N-ICU) of Xijing hospital. Among them, a total of 94 patients with SE were included in this study. The percentage of non-SRSE and SRSE were 76.6% and 23.4%. Cortical or hippocampal abnormality on neuroimaging (p = 0.002, OR 20.55, 95% CI 3.16 – 133.46) and END-IT score (p < 0.001, OR 4.07, 95% CI 1.91 – 8.67) are independent predictors of the progression to SRSE. At three months after N-ICU discharge, 56 (59.6%) patients attained good outcomes, and 38 (40.4%) patients had poor outcomes. The recurrence of clinical or EEG seizures within two hours after the infusion rate of a single anesthetic drug ＞ 50% proposed maximal dose (p = 0.044, OR 4.52, 95% CI 1.04 – 19.68), tracheal intubation (p = 0.011, OR 4.99, 95% CI 1.37 – 11.69) and cardiopulmonary resuscitation (p = 0.040, OR 9.80, 95% 1.11 – 86.47) predict poor functional outcome. Interpretation: Initial neuro-imaging findings assist early identification of the progression to SRSE. Continuous EEG monitoring contributes to outcome prediction in SE due to acute encephalitis.